Tempos Futuros - Reis, Zenir Campos (Revista do Instituto de Estudos Brasileiros, 1993)
Vidas secas (1938) is Graciliano Ramos last novel which was written after the autor´s experiences in the prisions of the Estado Novo. This experience was judged essential to the organization of the book by the author himself. The article begins with a discussion of the sense of ethica and aesthetic exigencies of the novelist. It endeavours to describe the organization of the novel, beginning with the combination of short stories which were originally autonomous works. Then it examines the episode "Baleia" where the problems of domestication and retaring are discussed. It finishes with the analysis of the tension beteween the talkof Utopia and critical realism